RELATIONSHIPS OF OWNERSHIP: ART AND THEFT IN BOB DYLAN’S 1960S TRILOGY - Rodgers, Michael (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
Bob Dylan’s corpus is one continually engaged with appropriation and pilfering. This paper will look, predominantly, at three songs from his 1960s’ trilogy – ‘She Belongs To Me’ from Bringing It All Back Home (1965), ‘Visions of Johanna’ from Blonde on Blonde(1966), and ‘Desolation Row’ from Highway 61 Revisited (1965) – arguing that, in these songs, Dylan problematizes the interrelationship between art, theft, and ownership. I argue that, similar to the urban artist Banksy, Dylan challenges, toys with, and appropriates cultural images in order to continually question the concept of proprietorship whilst rescuing cultural images from esoterica and attempting to put them back into the public domain.